Syntomatic Tarlov Cyst. Case presentation - Jorge Luis Castillo López; María E. Jerves Crespo; Victoria E. Solís Espín; Juan C. Vargas Parra (Medisur)
Tarlov or perineural cysts are pathologic deformations located in the space between the Perineurium and endoneurium of spinal roots close to the posterior root ganglion. It is an infrequent disease. Although its etiology is uncertain different theories have been postulated since its discovery. Regularly they are asymptomatic; they are discovered as incidental findings in imaging studies. A case is presented of a patient complaining of a lumbociatalgia of month evolution, without relation with previous efforts or traumas. Imaging studies allowed the diagnosis of Tarlov Cysts, which in this case presented atypically, so it could be confused with other affections of the lumbosacral level.